Cost-Effectiveness of Robotic vs. Laparoscopic Surgery for Different Surgical Procedures: Protocol for a Prospective, Multicentric Study (ROBOCOSTES) - Ielpo, Benedetto; Podda, Mauro; Burdio, Fernando; Sanchez-Velazquez, Patricia; Guerrero, Maria-Alejandra; Nuñez, Javier; Toledano, Miguel; Morales-Conde, Salvador; Mayol, Julio; Lopez-Cano, Manuel; Espín-Basany, Eloy; Pellino, Gianluca; et al. (Frontiers in Surgery, 2022)
Background The studies which address the impact of costs of robotic vs. laparoscopic approach on quality of life (cost-effectiveness studies) are scares in general surgery. Methods The Spanish national study on cost-effectiveness differences among robotic and laparoscopic surgery (ROBOCOSTES) is designed as a prospective, multicentre, national, observational study. The aim is to determine in which procedures robotic surgery is more cost-effective than laparoscopic surgery. Several surgical operations and patient populations will be evaluated (distal pancreatectomy, gastrectomy, sleeve gastrectomy, inguinal hernioplasty, rectal resection for cancer, Heller cardiomiotomy and Nissen procedure). Discussion The results of this study will demonstrate which treatment (laparoscopic or robotic) and in which population is more cost-effective. This study will also assess the impact of previous surgical experience on main outcomes.